Shortening the potential duration of unemployment benefits does not affect the quality of post-unemployment jobs: evidence from a natural experiment - Jan C. van Ours; Milan Vodopivec (Institute for the Study of Labor (IZA), 2006)
This paper investigates how the potential duration of unemployment benefits affects the quality of post-unemployment jobs. It takes advantage of a natural experiment introduced by a change in Slovenia's unemployment insurance law that substantially reduced the potential benefit duration. Although this reduction strongly increased job finding rates, the quality of the post-unemployment jobs remained unaffected: the paper finds that the law change had no effect on either the type of the contract (temporary vs. permanent), the duration of the post-unemployment jobs, or the wage earned in this job.
Keywords: C41; H55; J64; J65; 330; unemployment insurance; potential benefit duration; job separation rates; post-unemployment wages; Arbeitslosigkeit; Arbeitslosenversicherung; Lohnersatzleistungen; Dauer; Politische Reform; Lohn; Anforderungsprofil; Slowenien